La zona, una ciudad de México globalizada y colapsada por la violencia - Anzaldo-González, Demetrio (2013)
The disparities of social life as seen in the globalized Third world’s cities and urban spaces, have shown obvious symptoms of a terrible social decomposition that continues to worsen due to the lack of educational opportunities for their present and future citizenry. Violence, poverty, corruption, desperation, segregation and death are alarming factors affecting societies. Under this critical framework, the film, La zona, portrays different myths, memories and images lived in a collapsed Mexico City. The movie’s main theme is violence and its terrible consequences in Mexican society. La zona is part of the imminent apocalyptical era deserved for the human populations living in megalopolis such as Mexico City, enormous cities that tend to sacrifice the population of their youth.